(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2015)
This work examines a borate glass produced with oxides of potassium and lithium, known as LKB. The suitability of borate glasses for thermoluminescent (TL) dosimetry has been reported in previous studies. In particular, borate glasses doped with different elements showed good characteristics in terms of linearity, sensitivity and effective atomic number. However, borate glasses are also known to have high hygroscopicity, which can reduce the sensitivity of a dosimeter. Contrary to previous studies, in this work, Mg was used as one of the main components of the glass composition. Mg is known to improve the stability of the glass, since it reduces the mobility of the alkali ions and can thus reduce the hygroscopicity of the LKB glass. Three compositions containing 0, 5 and 11 mol% of magnesium oxide were examined in order to determine the effect of magnesium specifically on luminescence, high-temperature resistance and hygroscopicity of LKB glass. The LKB glass with 11 mol% of Mg showed favorable characteristics for the production of dosimeters.